Anisotropic nanowire growth via a self-confined amorphous template process: A reconsideration on the role of amorphous calcium carbonate - Mao, L.; Xue, L.; Gebauer, Denis; Liu, L.; Yu, X.; Liu, Y.; CÃ lfen, H.; Yu, S. (Tsinghua University Press, 2016)
Â© 2016, Tsinghua University Press and Springer-Verlag Berlin Heidelberg.Calcium carbonate crystals with various morphologies have been found in a variety of biospecimens and artificially synthesized structures. Usually, the diversity in morphology can be attributed to different types of interactions between the specific crystal faces and the environment or the templates used for the growth of CaCO3 crystals. On the other hand, isotropic amorphous calcium carbonate (ACC) has been recognized as the precursor of other crystalline calcium carbonate forms for both in vivo and in vitro systems. However, here we propose a self-confined amorphous template process leading to the anisotropic growth of single-crystalline calcite nanowires. Initiated by the assembly of precipitated nanoparticles, the calcite nanowires grew via the continuous precipitation of partly crystallized ACC nanodroplets onto their tips. Then, the crystalline domains in the tip, which were generated from the partly crystallized nanodroplets, coalesced in the interior of the nanowire to form a single-crystalline core. The ACC domains were left outside and spontaneously formed a protective shell to retard the precipitation of CaCO3 onto the side surface of the nanowire and thus guided the highly anisotropic growth of nanowires as a template. [Figure not available: see fulltext.]